Business Plan for Shaping Students’ Entrepreneurship Character and Competence - Lelahester Rina (Fakultas Ekonomi, Universitas Negeri Semarang, 2023)
This study aimed to analyze business plan activities as a strategy in entrepreneurship education in schools. Research used qualitative methods and the data were collected through in-depth interviews, non-participatory observation, documentation and triangulation of research data. The technique of selecting informants was through Snowball sampling consisted of students, teachers and several parties who were considered to understand the phenomena at Satya Wacana Junior and Senior Highschool. Analysis of the data used in this study was the analysis of the domain of Spradley by searching the domain and looking for semantic relationships. The results showed that the efforts made by school institutions in both junior and senior high school level could provide business plan methods that could shape the character and entrepreneurial competence. The characters formed in junior high school are: discipline, independence, creativity, responsibility, cooperation, hard work, risk taking, action orientation, and leadership. Competency consisted of communicative ability, being able to adapt to tasks, financial management and interpersonal skills. Other findings proved that high school students, through business plans, had characters: independent, creative, honest, curious, responsible, cooperative, hard work, tenacity, dare to take risks, curiosity, action oriented, leadership, commitment and orientation for success. Whereas the competence possessed were communicative, ability to solve problems, marketing ability, and interpersonal ability. The introduction of a business plan needs to be given continuously at all levels of education. School institutions can prepare curriculum, teaching materials, methods and strategies that can be integrated with entrepreneurial education.